Comparative sensitivity of proliferative and differentiated intestinal epithelial cells to the food contaminant, deoxynivalenol. (15th May 2021) - Luo, Su; Terciolo, Chloe; Neves, Manon; Puel, Sylvie; Naylies, Claire; Lippi, Yannick; Pinton, Philippe; Oswald, Isabelle P.
Abstract: The intestinal epithelium is a functional and physical barrier formed by a cell monolayer that constantly differentiates from a stem cell in the crypt. This is the first target for food contaminants, especially mycotoxins. Deoxynivalenol (DON) is one of the most prevalent mycotoxins. This study compared the effects of DON (0–100 μM) on proliferative and differentiated intestinal epithelial cells. Three cell viability assays (LDH release, ATP content and neutral red uptake) indicated that proliferative Caco-2 cells are more sensitive to DON than differentiated ones. The establishment of transepithelial electrical resistance (TEER), as a read out of the differentiation process, was delayed in proliferative cells after exposure to 1 μM DON. Transcriptome analysis of proliferative and differentiated exposure to 0–3 μM DON for 24 h revealed 4862 differentially expressed genes (DEG) and indicated an effect of both the differentiation status and the DON treatment. KEGG enrichment analysis indicated involvement of metabolism, ECM receptors and tight junctions in the differentiation process, while ribosome biogenesis, mRNA surveillance, and the MAPK pathway were involved in the response to DON. The number of differentially expressed genes and the amplitude of the effect were higher in proliferative cells exposed to DON than that in differentiated cells. In conclusion, our study shows that proliferative cells are more susceptible than differentiated ones to DON and that the mycotoxin delays the differentiation process. Graphical abstract: Image 1 Highlights: Intestinal proliferative cells are more sensitive to deoxynivalenol (DON) than differentiated cells. DON delays the establishment of TEER in proliferative cells. DON up-regulated genes involved in ribosome biogenesis, mRNA surveillance and MAPk. DON down-regulated genes involved in protein digestion and absorption, metabolic pathway and cholesterol metabolism. Upon DON exposure more genes are differentially expressed in proliferative cells than in differentiated ones. Abstract : Proliferative intestinal epithelial cells are more susceptible than differentiated ones, to DON.